Presence of by Escherichia coli in Pucusana Beach, Lima and its potential effect on public health - Huayanay Quevedo, Cinthia Milagros (2022)
Objective: To determine the values of the bacteria and fecal indicator Escherichia coli (EC) for seawater of safe and recreational use of the Pucusana beach, Lima. Materials and Methods: The campaigns of samplings were carried out once a week in the summer of 2019 and were processed in the microbiology laboratory of the Faculty of Biological Sciences (FCB) of the Ricardo Palma University using colimetry and the method of the most probable number (NMP). Results: The presence of EC was verified in all the analyzed samples, with average values higher than 1000 MPN/100 ml. in all collected samples. Conclusions: The lack of environmental health and its relevance in public health is demonstrated. The risk factors are produced mainly by the production and discharge of wastewater. residuals carried by the collectors to the sea and although an important proportion of these waters are processed at the PTAR Pucusana Wastewater Treatment Plant. Domestic and municipal discharges that discharge into the Pacific were identified, a problem that must have good management and environmental control because it deteriorates the environment and the seas.